PERBANDINGAN AKTIVITAS REPELAN ANTARA KRIM MINYAK ATSIRI JAHE (Zingiber offinale, Roxb) DENGAN KRIM MINYAK ATSIRI SERE (Cymbopogon citratus (D.C) Stapf) TERHADAP NYAMUK Aedes aegypti BETINA - Azis Ikhsanudin (Universitas Ahmad Dahlan, 2014)
The one efforts to prevent dengue fever is to prevent mosquito bites by using mosquitorepellent preparations. The nature of the toxicity of synthetic repellent be the reason for theresearch came from the plant. Sere and ginger into one of mosquito repellent plant because it contains of natural essential oils are many. The aim of this study was to determine the comparativeability repelan effects of essential oils cream sere (Cymbopogon citratus (DC) Stapf) and ginger(Zingiber officinale Roxb). The essential oil of sere (Cymbopogon citratus (DC) Stapf and ginger(Zingiber officinale Roxb), obtained by isolation of leaves and rhizome by steam distillation ofwater which is then tested physical properties including test of adhesion, test of spreadability andtest of mosquito repellent activities. The test of mosquito repellent activities using 20 birds Aedesaegypti mosquito female per cage with the using hand of women as volunteers as much as 4people. In this study were divided into sixth formulas of test. The sixth of cream formula withvariations in the concentration of essential oils sere and ginger wherein the formula I, II and IIIcontain essential oils sere as much as 20% v/w; 30% v/ w and 40% v/w, whereas for formula IV; V;and VI contain the essential oil of ginger as much as 6.25% v/w; 12.5% v/w and 25% v/w. Data ofphysical properties test were analyzed statistically using SPSS. The results showed the cream withthe concentration of essential oils sere 40% v/w (FIII) have better outcomes than others formulascream, where than of adhesion test is 0.46 ± 0.04 seconds; of the spreadibility test is 56.32 ± 14.78cm2 and repellent effect of 3014.2 ± 20.16 seconds.